Dietary total antioxidant capacity is inversely associated with the odds of non-alcoholic fatty liver disease in people with type-2 diabetes - Salavatizadeh, Marieh; Soltanieh, Samira; Poustchi, Hossein; Yari, Zahra; Shabanpur, Maryam; Mansour, Asieh; Khamseh, Mohammad E.; Alaei-Shahmiri, Fariba; Hekmatdoost, Azita (Frontiers in Nutrition, 2022)
Background This study was conducted to evaluate possible associations between Dietary Total Antioxidant Capacity (DTAC) and odds of non-alcoholic fatty liver disease (NAFLD) in people with type-2 diabetes mellitus (T2DM). Materials and methods We recruited two hundred people with T2DM, and evaluated their liver steatosis using Fibroscan. Dietary intakes of participants were assessed using a validated food frequency questionnaire. DTAC was computed via ferric reducing antioxidant power (FRAP). Results In the crude model, no statistically significant association was found between DTAC and the odds of NAFLD in people with diabetes. However, after adjustment for potential confounders including age, gender, diabetes duration, smoking status, physical activity, BMI, waist circumference, and energy, the most reduced adjusted OR was indicated for the third tertile vs. the first one (OR: 0.28, 95% CI: 0.09–0.81, P = 0.02), meaning that diabetic patients in the third tertile of DTAC had 72% decreased risk of NAFLD in comparison to those in the first one. The relationship was remained significant after additional adjustment for HOMA-IR, HbA1c, serum Triglyceride (TG), and low-density lipoprotein-cholesterol (LDL) levels (OR: 0.29, 95% CI: 0.09–0.93, P = 0.03). Importantly, a dose-response pattern was demonstrated for DTAC and risk of NAFLD (P = 0.04). Conclusion Higher DTAC was related with a decreased risk of NAFLD in individuals with diabetes.